PARTITIONING OF RARE EARTH ELEMENTS (REES) BETWEEN CALCITE AND SEAWATER SOLUTIONS AT 25°C AND 1 ATM, AND HIGH DISSOLVED REE CONCENTRATIONS - Zhong S.; Mucci A. (My University, 1995)
The partitioning of rare earth elements (REEs) in calcite overgrowths precipitated from sea-water solutions under steady-state conditions was investigated experimentally using a constant addition technique. The composition of the overgrowths and their parent solutions was determined by chelation and gradient ion chromatography (CGIC) and described using nonthermodynamic homogeneous partition coefficients. REEs are strongly partitioned into calcite and substitute for Ca2+. Their partition coefficients decrease systematically with atomic number, from # 103.6 for La3+ to # 101.9 for Yb3+ when their concentrations in solution are maintained at 70 nM. Under our experimental conditions, the partition coefficient of individual REEs was not affected by the calcite precipitation rate or [CO2-3] of the solutions. The partitioning of light REEs, however, was influenced by variations of their absolute solution concentrations.The partitioning behaviour of REEs is correlated to the solubility of their respective carbonate minerals. REE speciation in solution, adsorption on the surface of calcite, and subsequent reactions (e.g., dehydration) affect the partitioning process. Although the dissolved REE concentrations used in these experiments are exceptionally high for natural marine environments, the compatibility of our results with those obtained from field studies suggests that the partition coefficients derived from this study may have some potential for the interpretation of environmental, diagenetic, and paleoceanographic data.